The Impact of Oral and Written Feedback on EFL Writers With the Use of Screencasts - Roberto Alvira (Universidad Nacional de Colombia, 2016)
This article, based on an action research study performed at a Colombian middle-sized private university, proposes specific strategies to provide feedback to English as a foreign language learners and uses a Web 2.0 tool called screencasting. The findings of the study suggest that the use of coded, written, and oral feedback is widely accepted by students and yields positive results in the improvement of their writing skills at the paragraph level, and that the use of screencasting is a promising strategy that is motivational to students and increases the quality of their uptake.